The Specialization of Victimology: Science and Philosophy. To Specific Victimology - Hikal, Wael (2015)
Over the years born criminology that is responsible for studying the criminal phenomenon in all its aspects (made and individual), but being marginalized and attention victimology and victim present study can not forget the great link between both disciplines is not conceived as separate, ie, knowledge of criminal and especially their conduct should be compulsorily knowing, analyzing and comparing the personality and behavior that the victim observed during the development of crime.